2011
DOI: 10.21273/hortsci.46.6.932
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Nutrient Uptake, and Yield Promotion of Broccoli by Plant Growth Promoting Rhizobacteria with Manure

Abstract: This study was conducted to investigate the effects of root inoculations with Bacillus cereus (N2-fixing), Brevibacillus reuszeri (P-solubilizing), and Rhizobium rubi (both N2-fixing and P-solubilizing) on plant growth, nutrient uptake, and yield of broccoli in comparison with manure (control) and mineral fertilizer application under field conditions in 2009 and 2010. Bacterial ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 21 publications
7
53
0
1
Order By: Relevance
“…N uptake by the inoculated plants amended with PG was 1.9–2.5 times higher than that of the control plants, with the highest N uptake in inoculated plants treated with 10 g PG kg −1 . The enhanced N uptake by inoculated plants with growth‐promoting rhizobacteria applied in the current study could be associated with N fixation or promotion of root surface area, resulting in more nutrient depletion from the soil . Conversely to bacterial inoculations, applying organic manure to uninoculated soil decreased N concentration and uptake by maize shoots, mainly due to reduction of plant growth and the ability to absorb nutrients from the soil by increasing salinity level of the organically amended soil.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…N uptake by the inoculated plants amended with PG was 1.9–2.5 times higher than that of the control plants, with the highest N uptake in inoculated plants treated with 10 g PG kg −1 . The enhanced N uptake by inoculated plants with growth‐promoting rhizobacteria applied in the current study could be associated with N fixation or promotion of root surface area, resulting in more nutrient depletion from the soil . Conversely to bacterial inoculations, applying organic manure to uninoculated soil decreased N concentration and uptake by maize shoots, mainly due to reduction of plant growth and the ability to absorb nutrients from the soil by increasing salinity level of the organically amended soil.…”
Section: Resultsmentioning
confidence: 70%
“…The enhanced N uptake by inoculated plants with growth-promoting rhizobacteria applied in the current study could be associated with N fixation or promotion of root surface area, resulting in more nutrient depletion from the soil. 51 Conversely to bacterial inoculations, applying organic manure to uninoculated soil decreased N concentration and uptake by maize shoots, mainly due to reduction of plant growth and the ability to absorb nutrients from the soil by increasing salinity level of the organically amended soil. However, the treatments that combined both organic manure and microbial inoculation did not significantly change N concentration and its uptake compared with the control plants, indicating the importance of bacterial inoculation to inhibit adverse effects associated with organic manure.…”
Section: Treatment Effects On Plant Nutrient Concentrations and Uptakementioning
confidence: 98%
“…In an earlier study, PGPR inoculation resulted in salt tolerance by improved plant nutrient balance (Sheng et al 2011) and increased levels of N, P and K were recorded in raddish plants inoculated with Bacillus subtilis and Pseudomonas fluorescens (Mohamed and Gomaa 2012). The increase in nutrient concentration may also ascribe to increase in root surface area and modulated root exudation patterns (Adesemoye et al 2008) as observed in broccoli (Yildirim et al 2011). Likewise, Abou-Shanab et al (2006) reported that a low rhizospheric pH triggered the uptake of cationic nutrients.…”
Section: Discussionmentioning
confidence: 89%
“…In the present study, the increased nutrient uptake is likely due to increase in root surface area (offering more binding sites for nutrient binding) and subsequently root exudation as reported for broccoli plants (Yildirim et al . ). The root exudation improves the root microbial activity, leading to increased soil‐nutrient solubility and higher influx of nutrients into the plant roots (Ahemad and Kibret ).…”
Section: Discussionmentioning
confidence: 97%